Primary Paratesticular Leiomyosarcoma: A Case Report and Literature Review - Zeineb Naimi; Semia Zarraa; Salma Kammoun; Safia Yahyaoui; Maha Driss; Chiraz Nasr (Case Reports in Urology)
Paratesticular soft tissue sarcomas are very rare malignant mesenchymal tumors. With only few cases reported in the literature, data regarding diagnostic and management of these tumors are limited. We reported a case of primary paratesticular leiomyosarcoma in a 72-year-old man complaining of a progressively growing painless right scrotal mass. The patient underwent radical inguinal right orchiectomy and adjuvant 3D conformal radiotherapy to the tumor bed including the surgical scar. The prescription dose was 54 Gy, and no pelvic irradiation was performed. He remained free of recurrence for the last 16 months.